Short stay unit for patients in acute mental health crisis: A case‐control study of readmission rates. (27th December 2019) - Sveticic, Jerneja; Turner, Kathryn; Bethi, Shailendhra; Krishnaiah, Ravikumar; Williams, Lee; Almeida‐Crasto, Alice; Stapelberg, Nicolas J. C.; Roy, Samit
Abstract: Introduction: Past evaluations of psychiatric short stay units have shown positive outcomes for patients, yet very little is known about the factors related to readmissions. Methods: A Short Stay Pathway (SSP) has been introduced on the Gold Coast, Australia, for patients in acute mental health crisis with admissions of up to 3 days. Rates of readmissions within 28 days were compared for SSP patients (N = 678), and a diagnosis‐matched control group of patients from acute mental health beds (N = 1356). Demographic and clinical factors were considered as predictors of subsequent readmissions. Results: Average length of stay for SSP patients was 3.4 days, compared to 7.6 days in the control group. 10.6% of SSP patients and 18.4% of the control group were readmitted within 28 days ( P  < .001). For both groups, a 7‐day follow up significantly reduced readmissions ( P  < .05). Indigenous patients on SSP had higher odds of readmissions than non‐Indigenous patients ( P  < .05), and a diagnosis of a personality disorder increased readmission in the control group but not the SSP group ( P  < .001). Discussion: SSP reduced repeated hospitalizations for patients in acute crisis by 42%. An identification of factors related to future admissions can inform future tailoring of this model of care to subgroups of patients.